Activity of Ribosomes Containing 5S RNA with a Chemically Modified 3′-Terminus - Fahnestock, S. R. (1972)
Ribosomes containing 5S RNA in which the 3′-terminus has been modified chemically, either by periodate oxidation or by conversion of the terminal ribose to a morpholine derivative, are fully as active in peptidebond formation and polypeptide synthesis as those ribosomes with unmodified 5S RNA. These results exclude models for protein synthesis in which peptidyl-5S RNA is formed as an intermediate.